Neglected Rehabilitation: Challenges and Discrepancies in the Implementation of the Narcotics Law for Addicts in Ambon City - Rukiah Latuconsina; Patma Toisuta; Irham M. Jiat Latuamury; Emy Ollong; Ali Tamrin Wasolo (International Journal of Social Sciences and Humanities, 2026)
Rehabilitation for drug addicts is a treatment process aimed at freeing them from dependency, which is also considered a form of punishment. However, in Indonesia, particularly in Ambon City, Maluku Province, facilities for medical and social rehabilitation are still very limited. The rate of drug abuse in Maluku, especially in Ambon City, is relatively high, with 83 cases and 55 drug abuse patients recorded in 2021. Although Law Number 35 of 2009 on Narcotics mandates rehabilitation for addicts, its implementation in Ambon City has not been optimal due to the lack of facilities and specialized medical personnel. Rehabilitation involves three main stages: medical detoxification, non-medical rehabilitation, and follow-up guidance. However, in Ambon, rehabilitation is only conducted on an outpatient basis, without adequate inpatient facilities. Additionally, the lack of specialized medical personnel, such as psychiatrists and psychologists, hinders the effectiveness of the rehabilitation process. This contradicts the purpose of the Narcotics Law, which emphasizes rehabilitation as a means of healing rather than mere punishment. To improve the effectiveness of rehabilitation, the construction of permanent rehabilitation facilities and the enhancement of medical personnel quality are necessary. Furthermore, there needs to be a clear consensus in defining drug abusers, addicts, and victims of narcotics abuse to ensure appropriate legal handling and rehabilitation. Thus, rehabilitation can become a more humane and effective solution in addressing drug dependency issues in Ambon City and other regions in Indonesia.